One-pot neutron imaging of surface phenomena, swelling and diffusion during methane absorption in ethanol and n-decane under high pressure - Vopička, Ondřej; Číhal, Petr; Klepić, Martina; Crha, Jan; Hynek, Vladimír; Trtík, Karel; Boillat, Pierre; Trtik, Pavel (PLoS One, 2020)
We report a powerful method for capturing the time-resolved concentration profiles, liquid swelling and surface phenomena during the absorption of methane (CH4) in still liquid ethanol (C2D6O) and n-decane (n-C10D22) and at high spatial resolution (pixel size 21.07 μm) using neutron imaging. Absorption of supercritical methane was followed at two temperatures and two pressures of methane, namely 7.0, 37.8 °C and 80, 120 bar. Fick's second law, which was used in the liquid-fixed coordinates, enabled for an adequate parameterization of the observed concentration profiles and liquid levels using simple analytical expressions. For both studied liquids, anomalously slow diffusion was observed in the initial stage of the absorption experiment. This was ascribed to the slow formation of the surface excess on the interface, time constant ranged 130-275 s. The axial symmetry of the cell allowed for the tomographic reconstructions of the profiles of the menisci. Based on these profiles, contact angle and surface tension were evaluated using the Young-Laplace equation. Overall, neutron imaging made it possible to capture time- and space-resolved information from which the methane concentration, liquid level and meniscus shape under high-pressure conditions inside a cylindrical titanium vessel were quantitatively derived. Multiple characteristics of ethanol, a methane hydrate inhibitor, and n-decane, a model constituent of crude oil, were thus measured for the first time under industrially relevant conditions in a one-pot experiment.
Keywords: fyzikální jevy; alkany; zobrazení jednotlivé molekuly; Temperature; Petroleum; teplota; Neutrons; Methane; ethanol; Alkanes; neutrony; Single Molecule Imaging; Physical Phenomena; Models, Statistical; difuze; Diffusion; voda; ropa; statistické modely; Water; Ethanol; methan